Cultural Analysis of the Gaucha Community - Camargo Rodríguez, Leidy katerine
The article presents the results of an investigation about the trajectory of the Gaúcha culture located in the south of Brazil, in the state of Rio Grande do Sul. The work explains the historicity of the costumes and the evolution of different traditions to understand the current dynamics of this culture, one of the most diverse and complex populations in Brazil. The research was carried out through observation and immersion in the context, coexisting with native Brazilians. The processes of communication with non-native language within the academic community played a fundamental role in the analysis of cultural aspects, as well as the experience of understanding the nature of the customs and habits of the population. It is hoped that the experience will contribute to enrich cultural knowledge.